Curriculum Design for Ecotourism with an Environmental Literacy Approach in Higher Education: A Qualitative Study - Alipour Torbati, Zohreh; Soleimanpour Omran, Mahboobeh; Esmaeilishad, Behrang (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to explain and identify the design of an ecotourism curriculum with an environmental literacy approach in higher education. Methodology: The research design was qualitative, specifically a qualitative case study. In this context, faculty members from the fields of curriculum planning, social sciences, and environmental studies at selected universities were considered as expert participants. Using a purposive sampling approach, key informants were selected, and semi-structured interviews were conducted with 17 individuals until theoretical saturation was reached. The data obtained were analyzed using thematic analysis. Reliability was ensured through retesting and intra-subject agreement methods, while validity was confirmed through expert review and content validity checks. The findings were organized into themes. Findings: Based on the results, a matrix framework of curriculum elements (objectives, content, teaching methods, and assessment) was developed. Five organizing themes and 76 basic themes were identified, and a thematic network was extracted. The curriculum design for a "green curriculum" in the Iranian education system (as an overarching theme) and the organizing themes encompassing five dimensions: objectives, content, teaching methods, assessment, and skills and competencies, were highlighted. Each category contains various dimensions within the basic themes, which were organized as the ecotourism curriculum with an environmental literacy approach in higher education. Conclusion: The findings of this study provide the foundation for implementing an ecotourism curriculum with an environmental literacy approach in higher education.